Analisis Faktor Keberhasilan Sistem Informasi Manajemen Puskesmas (SIMPUS) di Indonesia: Systematics Literature Review - Haqi Achmad F; Layla Mazidatus S; Aliyyah Nabiilah F; Novita Fitriana (Lembaga Pengembangan Kinerja Dosen, 2023)
The Puskesmas Management Information System is a system arrangement that provides information to assist the decision-making process of the Puskesmas management. SIMPUS aims to facilitate and improve the quality of puskesmas health services. However, SIMPUS implementation in Indonesia is still faced with various challenges and obstacles. To measure the success factors for SIMPUS performance, a Systematic Literature Review is conducted on each paper that has a similar research topic. From the Systematic Literature Review, it was found that there were several problems that occurred when using SIMPUS, such as the required data and information were not available on time. This can be caused by several factors, including technical factors, organizational factors, human factors and environmental factors. The research method that is often used in SIMPUS evaluation research is a type of qualitative research with data collection methods through interviews with employees who operate SIMPUS.